Quantifying network flexibility requirements in terms of energy storage - Nayak-Luke, R; Bañares-Alcántara, R; Collier, S (Elsevier, 2020)
The energy storage requirement modelling tool outlined here uses an extension of the pinch methodology to quantify the network flexibility required due to greater variable renewable energy (VRE) integration. Quantifying this as the magnitude of energy storage required as a function of storage duration provides improved understanding of the fundamental balancing problem. Identification of the impact that key decision variables, such as location, VRE penetration and VRE that is supplied through wind have on these requirements has been enabled by condensing this dependence within two non-dimensional indices: the storage magnitude index and the storage duration index. These indices, in addition to the size of storage required, have enabled the tipping-points and VRE penetration levels beyond which short-term storage is not sufficient to be identified for the UK and Australian locations considered. In addition to how effective the provision of excess VRE is in the mitigation of the balancing requirements. This analysis shows that seasonal balancing is required at high levels of VRE penetration for all combinations of wind and solar sources, but can be needed with as low as 50% penetration at certain combinations and locations. The tipping-point is highly specific to location and VRE that is supplied through wind, varying between 30% and 50% of VRE penetration.